1975
DOI: 10.1007/bf00158459
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure and temporal development of a solar X-ray flare observed from Skylab on June 15, 1973

Abstract: A solar flare on June 15, 1973 has been observed with high spatial and temporal resolution by the S-054 grazing-incidence X-ray telescope on Skylab. Both morphological and quantitative analyses are presented. Some of the main results are: (a) the overall configuration of the flare is that of a compact region with a characteristic size of the order of 30" at the intensity peak, (b) this region appears highly structured inside with complex systems of loops which change during the event, (c) a brightening over an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…(3) SXR brightenings Roy and Tang (1975) studied six flares and found that SXR bursts often accompany the preflare expansion of the filaments. Such a phenomenon was studied by several researchers (Pallavicini et al, 1975;Rust et al, 1975;Webb et al, 1976). As an extension, Simnett and Harrison (1985) studied the relation between the preflare activity and CMEs, and found that there is usually a weak SXR enhancement 15 -30 min prior to the linearly extrapolated onset time of the CMEs, which was called SXR precursors for CMEs.…”
Section: Observational Precursorsmentioning
confidence: 99%
“…(3) SXR brightenings Roy and Tang (1975) studied six flares and found that SXR bursts often accompany the preflare expansion of the filaments. Such a phenomenon was studied by several researchers (Pallavicini et al, 1975;Rust et al, 1975;Webb et al, 1976). As an extension, Simnett and Harrison (1985) studied the relation between the preflare activity and CMEs, and found that there is usually a weak SXR enhancement 15 -30 min prior to the linearly extrapolated onset time of the CMEs, which was called SXR precursors for CMEs.…”
Section: Observational Precursorsmentioning
confidence: 99%
“…Since the Skylab era (Zirin & Tanaka 1973;Pallavicini et al 1975) it has been clear that later loops in the gradual phase of a flare look more potential-like, and make a larger angle to the neutral line, and this is often glibly taken as evidence for the reduction of shear expected to reduce the stored magnetic energy. Clearly it is not that simple; the observed changing pattern of shear is determined by the amount of shear in the pre-flare field as a function of distance from the neutral line before the flare, as well as its reduction as a function of time during the flare.…”
Section: Flare Footpoints and The Magnetic Environmentmentioning
confidence: 99%
“…The relatively flat spectrum of the t w o -r i b b o n sources suggests their thermal origin. Hudson andOhki (1972) andShimabukuro (1972) have carried out a quantitative comparison between soft X-ray bursts and associated microwave gradual bursts with fiat spectra, and have confirmed Kawabata's (1960) hypothesis that both soft X-ray and microwave emissions originate from common hot (-107 K), condensed ( -1 0 1~…”
Section: Summary and Discussionmentioning
confidence: 58%
“…Further confirmation of this hypothesis has been made by Pallavicini et al (1975) using high-resolution soft X-ray images of a flare obtained with the S054 telescope aboard Skylab. The t w o -r i b b o n sources of the present event have undoubtedly a thermal …”
Section: Summary and Discussionmentioning
confidence: 68%